To solve for the missing exponent in the equation \( \frac{h^{450}}{h^?} = h^{215} \), we can use the properties of exponents.
The rule for dividing exponents with the same base states that:
\[ \frac{a^m}{a^n} = a^{m-n} \]
Applying this rule, we can rewrite the left side of the equation:
\[ \frac{h^{450}}{h^?} = h^{450 - ?} \]
Now we set this equal to the right side of the original equation:
\[ h^{450 - ?} = h^{215} \]
Since the bases (h) are the same, we can set the exponents equal to each other:
\[ 450 - ? = 215 \]
Now, to find the missing exponent (?), we rearrange this equation:
\[ ? = 450 - 215 \] \[ ? = 235 \]
Therefore, the missing exponent is \( 235 \).